Mathematical Dynamic Model for Long-Term Distribution System Planning - Mikic, Obrad M. (IEEE transactions on power systems, 1986)
The presented model gives optimal values of all distribution system design parameters for a consumption area without existing network, in which uniform load density increases with time. The model belongs to a class of nonlinear mixed integer programming tasks, subject to nonlinear constraints. Transformation of dynamic problem into nondynamic form is performed using a defined planning strategy. Objective function of the model is the present value of system investment, maintenance and energy loss costs within a planning period. The constraints, among others (thermal, integer), are the permitted voltage drops in lines. The solution algorithm is described and results of model application for a rural area are given.